2011
DOI: 10.1021/es203286e
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-Carrying Electrospun Fibrous Membranes for Adsorption and Degradation of PAHs in Shoal Soils

Abstract: The removal of polycyclic aromatic hydrocarbons (PAHs) from soil is costly and time-consuming. The high hydrophobicity of PAHs makes PAH diffusion from soil particles by hydraulic flow difficult. The phase transfer of PAHs from soil to another available mediator is crucial for PAH removal. This study focuses on the remediation of PAH-contaminated shoal soil, located in Yangtze, China, using three types of laccase-carrying electrospun fibrous membranes (LCEFMs) fabricated via emulsion electrospinning. These LCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 34 publications
7
60
0
Order By: Relevance
“…The activity of immobilized Lac was clearly stabilized compared with that of free Lac. Similar results have been reported for other nanobiocatalysts [37,38].…”
Section: Stability Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The activity of immobilized Lac was clearly stabilized compared with that of free Lac. Similar results have been reported for other nanobiocatalysts [37,38].…”
Section: Stability Analysissupporting
confidence: 91%
“…Similar results have been reported for catalase covalently bound to electrospun nanofiber meshes filled with carbon nanotubes [40]. It was also reported that the conducting carbon nanotubes were able to promote direct electron transport from redox enzymes such as ascorbate oxidase, peroxidase, and Lac [38,[40][41][42][43][44][45][46]. Therefore, PpPD/Fe3O4 nanocomposite may also be suitable for enzyme immobilization, especially for redox enzymes.…”
Section: Removal Of Rb-19supporting
confidence: 80%
“…The ANT removal by immobilized mycelia was a thirdorder reaction indicating that the process could be affected by multiple factors. Similar results were observed by a recent report with respect to the removal of PAHs by laccase-carrying electro spun fibrous membranes [33]. Compared with the immobilized mycelia in CA/PCL and CA beads, the removal rate of ANT by the immobilized mycelia in CA/PCL/corn-cobs was much faster.…”
Section: Kinetics Parameter Antsupporting
confidence: 91%
“…It has been reported that the immobilized laccase in most hydrophobic matrices showed the lowest retained activity as the hydrophobic matrices might undermine the conformation stability of laccase [33]. The results confirmed that CA/12% PCL bead was a suitable immobilization system for laccase.…”
Section: The Optimum Concentration Of Pclsupporting
confidence: 62%
See 1 more Smart Citation